Empowering Agility Among Tedung Craftsmen: A Community-Based Participatory Approach in Mengwi, Bali - Ida Ketut Kusumawijaya; Partiwi Dwi Astuti; I Made Hedy Wartana; I Ketut Yudana Adi (International Journal Of Community Service, 2025)
This community service initiative addresses the critical need for employee agility among 27 tedung craftsmen in Mengwi, Badung, Bali, whose traditional skills are challenged by evolving market demands. Recognizing that demographic factors such as gender, age, education, and work experience significantly influence agility in these crafts, this project aimed to enhance adaptability through targeted empowerment and capacity-building workshops. The objective was to bolster the craftsmen’s responsiveness to market conditions, customer needs, and technological changes while fostering a community-wide model of cross-generational skill exchange. The methodology employed participatory action research, engaging craftsmen through structured workshops focusing on adaptability in customer interactions, agility in market responses, and digital skill acquisition. The community-based approach emphasized experiential learning and skill mentorship, allowing younger craftsmen to integrate traditional techniques with modern agile practices. Data was gathered through pre-test and post-test assessments, evaluating agility across ten dimensions, including responsiveness, innovation in management skills, and decision-making autonomy. The results demonstrated substantial improvements across all dimensions of workforce agility, with notable gains in customer responsiveness and adaptability to market fluctuations. Mean scores for agility indicators shifted significantly from pre-intervention levels, underscoring the effectiveness of community-centered training in enhancing adaptability. For instance, scores related to responsiveness to changing customer needs and market conditions doubled, indicating that craftsmen could better align their practices with consumer expectations and external market shifts. Additionally, cross-generational mentoring promoted the sharing of traditional skills alongside agile competencies, ensuring sustainability in the tedung craft sector. These findings highlight the potential of participatory training to bridge agility gaps in traditional communities, offering a replicable model for enhancing adaptability in other craftsmen sectors. The project’s success demonstrates that community-focused agility interventions can sustain traditional crafts by aligning them with contemporary market demands. Future initiatives could expand on this foundation by incorporating advanced technical training and exploring broader applications in diverse cultural settings, thus fostering resilience in traditional craftsmanship amid modern economic landscapes.